ARTIFICIAL INTELLIGENCE AND HUMAN CREATIVITY: COMPETITION OR COLLABORATION? - Baxarova, Asila (University Research Base, 2025)
Artificial intelligence (AI) has significantly influenced various fields in recent еars, particularly in creative industries such as art, music, literature, and design. This paper explores the interaction between AI and human creativity, questioning whether AI serves as a competitor or a valuable tool for collaboration. The study focuses on how AI can augment and enhance human creativity, rather than replace it. By examining case studies and applications in creative fields, the research discusses how AI technologies are integrated into creative processes, providing new opportunities for artists, musicians, and writers. The paper argues that AI should not be viewed as a threat to human creativity but as a partner that can enhance the creative potential of human creators. The findings suggest that collaboration between AI and humans can lead to groundbreaking innovations and new forms of artistic expression. However, the study also addresses ethical concerns, such as authorship, originality, and the implications of AI-generated works. In conclusion, AI has the potential to transform creative industries, but its success depends on how it is used to collaborate with human creators rather than replacing them. This research offers insights into the future of creativity in an AI-driven world, advocating for a harmonious relationship between technology and human ingenuity.